2018
DOI: 10.1158/1538-7445.am2018-667
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 667: The radioprotector GC4419 ameliorates radiation induced lung fibrosis while enhancing the response of non-small cell lung cancer tumors to high dose per fraction radiation exposures

Abstract: Stereotactic Ablative Radiotherapy (SAbR) has revolutionized the treatment of non-small cell lung cancer (NSCLC). Despite these advances, treatment-limiting normal tissue toxicities preclude the use of fully potent radiation prescriptions in large or centrally located tumors. Radiation-induced lung fibrosis (RILF), thought to be generated by the production of superoxide in irradiated tissues, is a natural target for agents to limit RILF and thus allow for fully potent SAbR. Superoxide dismutase (SOD) catalyzes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Also, like M40403, Sishc has demonstrated that avasopasem is effective at preventing and mitigating radiation normal tissue toxicity in mouse models of radiation-induced pulmonary fibrosis and oral mucositis. 46 , 47 Intriguingly, these reports also suggest potential for avasopasem in the particularly refractory setting of reirradiation. In addition, the question of whether older cancer patients are more susceptible to treatment toxicities has been ongoing for many years, with potential relevance in HNC radiation therapy given the age of some patients.…”
Section: M40403 and Avasopasem Manganese (Gc4419) In The Mitigation Omentioning
confidence: 91%
See 1 more Smart Citation
“…Also, like M40403, Sishc has demonstrated that avasopasem is effective at preventing and mitigating radiation normal tissue toxicity in mouse models of radiation-induced pulmonary fibrosis and oral mucositis. 46 , 47 Intriguingly, these reports also suggest potential for avasopasem in the particularly refractory setting of reirradiation. In addition, the question of whether older cancer patients are more susceptible to treatment toxicities has been ongoing for many years, with potential relevance in HNC radiation therapy given the age of some patients.…”
Section: M40403 and Avasopasem Manganese (Gc4419) In The Mitigation Omentioning
confidence: 91%
“…Mitigation of any supportive care indication which is based on the protection of normal cells from a cytotoxic challenge comes with the hypothetical risk that tumor tissue may also be protected. Earlier animal model studies have suggested that avasopasem not only does not decrease the anti-cancer efficacy of radiation, but with higher dose per fraction can increase it substantially 46 and, while simultaneously protecting the mucosa can enhance tumor kill following radiation and immunoradiotherapy. 47 In 2020, Anderson reported that long-term follow-up of Phase 2b participants confirmed that GC-4419 did not negatively impact tumor response (overall survival, progression-free survival, locoregional control, distant metastases) one and two years 55 , 56 following treatment.…”
Section: M40403 and Avasopasem Manganese (Gc4419) In The Mitigation Omentioning
confidence: 99%